Utilization of Arduino UNO Technology and Arduino IDE to Create Electrical Disconnect Products for Electronic Equipment - Dwi Iskandar; Ahmad Sunandar (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
Today many people often forget to turn off household appliances such as fans or lights, which results in the flow of electricity from the socket even when not in use, resulting in excessive power consumption. Electricity tariff for the first quarter of 2019: IDR 1,115 / kWh for medium voltage customers. If the lecture room has 4 lamps where each lamp has 23 watts of power, 2 Daikin AC units with 1 PK each, each air conditioner has 840 watts of power. Acer S1213Hn LCD projector has the power: 250 Watt, the total cost of electricity consumption per hour and usage for a month of 26 days for the lecture hall consisting of lamps, air conditioner and LCD projectors is IDR 58,617.78. The research method used is literature study and data collection, technology concept design, development preparation, hardware assembly, Arduino UNO coding, upload coding to hardware, technology testing. To find out the test results whether the technology can work properly, it must be applied directly by connecting the technology that has been created with electricity directly. The way that can be done is to connect the Arduino with mains power using a DC 5 V adapter then connect the relay to a 220 V AC power source and a 220 V halogen lamp. After everything is connected, the lights can be turned on by bringing the registered RFID closer to the RFID Reader, if you want. set how long it takes for the light to turn on can press a button on the IR remote